Advancing technologies for Asian business and economics information management developments - Ura, Dasho Karma, 1961-; Ordóñez de Pablos, Patricia, 1975- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book offers the latest research available within the field of information management as it pertains to the Asian business market, promoting and coordinating developments in the field of Asian and Chinese studies, as well as presenting strategic roles of IT and management towards sustainable development"--Provided by publisher.